Understanding the role of spirituality during COVID-19: A cross-cultural qualitative analysis - Waila K; Lindsay N (Taylor and Francis Group, 2024)
The novel coronavirus disease (COVID-19) outbreak in 2019 brought widespread disruptions to normal daily functioning. The current qualitative phenomenological study explored the role of spirituality during the pandemic across two divergent cultural contexts; India and New Zealand. Inductive thematic analysis of results revealed that spirituality was found to entail a range of convergent health and wellbeing effects that were categorised into four major themes; hope, meaning amidst chaos, strengthened mental fortitude, and inner transformation. Overall, spirituality provided individuals a range of tools to navigate the crisis, building individual resilience and providing courage to face the pandemic’s most difficult challenges. Moreover, the inner-transformative effects of spirituality fostered significant post-traumatic growth above and beyond the immediate impacts of the event, providing evidence for the therapeutic potential inherent within spirituality.
Keywords: COVID-19; pandemic; resilience; Spirituality; wellbeing